A Comparative Study Between the Cultural Level of Dietary Patterns on the Immune System Among Girls of PAAET at the College of Basic Education in Kuwait and the Faculty of Specific Education, Mansoura University, Egypt - Al Shammari, Ali Monahi Nazal; El-Mehiry, Hanaa F. (European Journal of Applied Sciences, 2025)
Supporting immune function requires a healthy lifestyle, adequate water intake, and essential minerals like magnesium and zinc, as well as vitamin C, D, and E. The purpose of this study was to examine the impact of dietary patterns on the immune system by assessing whether undergraduate students met the recommended dietary intake. The research focused on students from the College of Basic Education in Kuwait andthe Faculty of Specific Education at Mansoura University, Egypt, during the academic year 2024–2025. This cross-sectional study involved 150 undergraduate students from the two universities mentioned above. Students completed a 72-hour dietary recall and a questionnaire at (0, 6, and 12 week). A self-administered questionnaire was used to collect data, which included questions on anthropometric measures and eating habits. Results indicated in students’ subjects at (0, 6,and 12 weeks) and demonstrated that the mean intakes of water, total fiber, magnesium, calcium, vitamins (B6, E, D)folate, and all essential amino acids were lower than dietary reference intake. Moreover, the university population consumed a diet with too many calories, carbohydrates,proteins and fats as compared to dietary reference intake at (0, 6, and 12 weeks). Moreover, the results show that overweight and obesity were common among students, with more than 20% classified as overweight or obese, and the majority having unhealthy eating habits. These results increased the probability of developing dysfunction in the immune system and noncommunicable diseases. Thus, it is necessary to introduce an organized nutrition education program aimed at new students.